Surveillance and management of hepatocellular carcinoma after treatment of hepatitis C with direct-acting antiviral drugs - Yang, Caiyun; Lv, Fengxiang; Yang, Jiaqi; Ding, Dawei; Cui, Lina; Han, Ying (Annals of hepatology, 2025)
Hepatitis C virus (HCV) belongs to the Flaviviridae family, and is a single-stranded RNA virus with positive polarity. It is the primary cause of hepatocellular carcinoma (HCC) worldwide. The treatment of HCV has entered a new era with the advent of direct-acting antiviral drugs (DAAs) and is associated with cure rates of more than 95 %, making HCV the only curable viral disease. The successful treatment of chronic hepatitis C has greatly reduced, but not eliminated, the risk of HCC. Certain individuals, especially those with cirrhosis already present, remain vulnerable to HCC after achieving a sustained virological response (SVR). This article systematically reviews the recent studies on the risk and mechanisms of HCC development after HCV viral cure, the screening and predictive value of biological markers, and patient surveillance. Factors such as older age, diabetes, hepatic fat accumulation, alcohol use, and lack of fibrosis reversal are linked to increased HCC risk after HCV cure. The mechanism of HCC development after DAAs treatment remains unclear, but the possible mechanisms include immune cell dysfunction during HCV infection, cytokine network imbalance, epigenetic alterations, and host factors. Several biological markers and risk prediction models have been used to monitor the risk of HCC in CHC patients who have achieved SVR, but most still require validation and standardization. The implementation of risk-stratified surveillance programs is becoming urgent from a cost-effective point of view, but the availability of validated biomarkers to predict HCC in cured patients remains an unmet clinical need. Additionally, managing CHC patients who achieve SVR is becoming a growing challenge as an increasing number of HCV patients are cured.